CORRELATION OF PROGESTERONE AND CORTISOL PLASMA LEVELS BETWEEN OVULATED AND NON-OVULATED ETTAWA CROSSBREDS DOES - Astuti, Pudji; Tri Widayati, Diah; -, Sunendar; Suharto, Kresno; Kusumawati, Asmarani; Junaidi, Aris (Jurnal Veteriner; Vol 9 No 1 (2008))
This experiment was conducted to determine the correlation of progesterone and cortisol levels in plasma between ovulated and non-ovulated Crossbreds Ettawa does. Eight does were used in this experiment and they were divided equally into 2 groups, i.e. group I consisting of 4 normal ovulated does with the average body weight of 37.5 ± 3.109 kg and group II consisting of 4 non-ovulated does with the average body weight of 28 ± 2.160 kg as group II. The estrus cycles of all does were synchronized using intravaginal device of controlled internal drug release (CIDR) accompanied by intra-muscular injection of prostaglandin F2 (PGF2) alpha. Immediately after the onset of estrus, blood samples were collected from jugular every 3 and 6 hours for 72 hours after onset of estrus. The concentration of cortisol and progesterone in plasma was assayed by enzyme linked immunosorbent assay (ELISA). The results showed that the average concentrations of cortisol in ovulated does (90.89±26.22 ng/mL) was higher than in non-ovulated does (42.70±37.18 ng/mL). Similarly, the concentrations of progesterone in ovulated does (0.098±0.0423 ng/mL) was higher than in non-ovulated does (0.093±0.056 ng/mL). It was evident that the change in progesterone level was closely associated with the change in cortisol level in plasma.
Keywords: progesterone, cortisol, ovulated, non-ovulated, does